2021
DOI: 10.3389/fnsys.2021.666649
|View full text |Cite
|
Sign up to set email alerts
|

Cortico-Cerebellar Hyper-Connections and Reduced Purkinje Cells Behind Abnormal Eyeblink Conditioning in a Computational Model of Autism Spectrum Disorder

Abstract: Empirical evidence suggests that children with autism spectrum disorder (ASD) show abnormal behavior during delay eyeblink conditioning. They show a higher conditioned response learning rate and earlier peak latency of the conditioned response signal. The neuronal mechanisms underlying this autistic behavioral phenotype are still unclear. Here, we use a physiologically constrained spiking neuron model of the cerebellar-cortical system to investigate which features are critical to explaining atypical learning i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 100 publications
(156 reference statements)
0
3
0
Order By: Relevance
“…For example, simulations predicted that alterations of synaptic plasticity in the cerebellar cortex could impair EBCC in different forms of cerebellar ataxia and that synaptic plasticity in the deep cerebellar nuclei was a possible compensatory mechanism ( Geminiani et al, 2018a ). Moreover, in autism spectrum disorder, simulations suggested that a higher CR learning rate could reflect a reduced number of Purkinje cells ( Trimarco et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, simulations predicted that alterations of synaptic plasticity in the cerebellar cortex could impair EBCC in different forms of cerebellar ataxia and that synaptic plasticity in the deep cerebellar nuclei was a possible compensatory mechanism ( Geminiani et al, 2018a ). Moreover, in autism spectrum disorder, simulations suggested that a higher CR learning rate could reflect a reduced number of Purkinje cells ( Trimarco et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The current model represents a first important step to study the possible integration of reinforcement and supervised learning processes in the brain. Future versions of the model could increase the realism and the quantitative matching of data of the model by including features that reproduce the interaction between cortical-subcortical learning mechanisms [70,71], and an architecture more closely reproducing the brain hierarchy underlying the acquisition and expression of motor movements with possibly a more explicit representation of targets [72][73][74].…”
Section: Discussionmentioning
confidence: 99%
“…These cerebellar neurons send inhibitory projections to the deep cerebellar nuclei (the output nuclei of the cerebellum) and the posterior lobe of the Vermis. Loss of these neurons is thought to lead to disinhibition of the deep cerebellar nuclei and of the uvula/nodulus lobules (Cerliani et al, 2015; Belmonte et al, 2004), which could explain the observed increased cerebellar integration and consequent abnormal eyes movement control in ASD patients (Trimarco et al, 2021).…”
Section: Discussionmentioning
confidence: 99%